Association Between Vitamin D Status and Diabetic Complications in Patients With Type 2 Diabetes Mellitus: A Cross-Sectional Study in Hunan China - Xiao, Ying; Wei, Ling; Xiong, Xiaofen; Yang, Ming; Sun, Lin (Frontiers in Endocrinology, 2020)
Background: Vitamin D status has been linked to diabetes-related complications due to multiple extraskeletal effects. We aimed to investigate the association between vitamin D deficiency (VDD) and diabetic vascular complications, including diabetic retinopathy (DR), diabetic kidney disease (DKD), and diabetic foot ulcers (DFU). Methods: A total of 4284 Chinese patients with type 2 diabetic mellitus (T2DM) were enrolled into the cross-sectional study. VDD was defined as serum 25-hydroxyvitamin D <50 nmol/L. Demographic data, physical measurements, laboratory measurements, comorbidities, and related medications were collected and analyzed by VDD status. Poisson regression with robust variance estimation and binary logistic regression were performed to explore the relationship between VDD and diabetic complications. Results: The prevalence of VDD, DR, DKD, DFU accounted to 71.7% (95% confidence intervals [CI]: 70.3%-73.0%), 28.5% (95% CI: 27.2%-29.9%), 28.2% (95% CI: 26.8%-29.5%) and 5.7% (95% CI: 5.1%-6.5%), respectively. The prevalence ratios (95% CI) for DR and DKD by VDD status, adjusted for demographics, physical measurements, laboratory measurements, related complications and comorbidities, and medications, were 1.093 (0.983-1.215) and 1.041 (0.937-1.156), respectively. The odds ratio (95% CI) for DFU by VDD status was 1.656 (1.159-2.367) in the final adjusted model. Meanwhile, the prevalence of VDD was significantly higher in patients with DFU compared with patients without DFU. Conclusions: The present study firstly indicated that VDD was significantly associated with a higher prevalence of DFU among Chinese T2DM patients. The association between VDD status and DR or DKD was not significant when adjusting for all potential covariates. Vitamin D screening or supplementation may be beneficial to prevent diabetic complications and improve the prognosis of T2DM patients.